Kandungan Fitokimia Daun Duku Kumpeh dan Manfaatnya Bagi Kesehatan Dia - Dian Novita; Ardi Mustakim (CV. Muara Edukasi, 2026)
Kumpeh duku leaves are part of a local duku plant that has traditionally been used by communities as a natural medicinal resource. Various literature sources indicate that Kumpeh duku leaves contain diverse phytochemical compounds that potentially provide health benefits. The phytochemical components commonly found in duku leaves include flavonoids, alkaloids, saponins, tannins, and phenolic compounds. These compounds are known to exhibit biological activities that support the maintenance of body functions. This literature review aims to examine the phytochemical content of Kumpeh duku leaves and their health benefits based on previous studies. The review results indicate that flavonoids and phenolic compounds in duku leaves act as antioxidants that help protect body cells from damage caused by free radicals. In addition, alkaloids and saponins are reported to possess antibacterial and anti-inflammatory activities that may inhibit the growth of pathogenic microorganisms and reduce inflammation. Kumpeh duku leaves are also suggested to support digestive health, enhance the immune system, and help regulate blood glucose levels. Based on the literature review, it can be concluded that Kumpeh duku leaves have significant potential as a natural source of phytochemical compounds beneficial to health. The proper utilization of Kumpeh duku leaves may be developed as an alternative herbal resource to support community health improvement